2017
DOI: 10.1080/23802359.2017.1325345
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of the threatened trident maple Acer buergerianum (Aceraceae)

Abstract: Trident maple Acer buergerianum Miq., belonging to the family of Aceraceae, is an important ornamental tree. Here, we report the complete chloroplast genome sequence of A. buergerianum . The circular genome was 156,477 bp in size, and comprised a pair of inverted repeat (IR) regions of 26,090 bp, a large single-copy (LSC) region of 86,246 bp and a small single-copy (SSC) region of 18,062 bp. It contained 134 genes, including 89 protein-coding genes, 40 transfer RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The largest and smallest chloroplast genomes of Acer miaotaiense were found in Zhangliangmiao, Liuba country (ZL) and Dianbingchang, Meixian country (DB) with lengths of 156,260 bp and 156,204 bp, respectively ( Table 1 ). The structure of the cp genome of Acer miaotaiense was similar to those from the other Acer species, such as Acer buergerianum [ 15 ], Acer morrisonense [ 16 ], and Acer davidii [ 17 ], in terms of genome size and the length of the four main regions.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The largest and smallest chloroplast genomes of Acer miaotaiense were found in Zhangliangmiao, Liuba country (ZL) and Dianbingchang, Meixian country (DB) with lengths of 156,260 bp and 156,204 bp, respectively ( Table 1 ). The structure of the cp genome of Acer miaotaiense was similar to those from the other Acer species, such as Acer buergerianum [ 15 ], Acer morrisonense [ 16 ], and Acer davidii [ 17 ], in terms of genome size and the length of the four main regions.…”
Section: Resultsmentioning
confidence: 64%
“…These results showed that, for the cp genome of Acer miaotaiense , the number of genes and protein-coding genes is quite conserved across the five studied geographical locations. The total number of genes was slightly lower than that for some Acer species, such as Acer davidii Franch (134 genes) [ 17 ], and Acer buergerianum (134 genes) [ 15 ], but with a higher number of protein-coding genes. During the evolution of angiosperms, multiple gene losses remain an ongoing process [ 10 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…wangii has 135 [58], A . buergerianum has 134 [59], and in Meliaceae species has 112 genes [60], which is from the same order Sapindales [51]. Camellia species contains 146 genes [60].…”
Section: Resultsmentioning
confidence: 99%
“… 2019 ), and A. buergerianum (Xu et al. 2017 ). In the present study, the complete chloroplast genome of A. ginnala was assembled, annotated, and analyzed phylogenetically.…”
mentioning
confidence: 99%
“…The chloroplast genome is highly conserved among plant species and can provide important molecular data for phylogenetic research, biogeographical research, and genetic diversity research (Abla et al 2019). At present, chloroplast sequencing and annotation of several Acer plants have been conducted, including A. cinnamomifolium , A. truncatum (Chen, Liu et al 2019), and A. buergerianum (Xu et al 2017). In the present study, the complete chloroplast genome of A. ginnala was assembled, annotated, and analyzed phylogenetically.…”
mentioning
confidence: 99%